Effect of Alkyl Chain Length of Quaternary Ammonium Salts on Pure Size Distribution and Surface Area of Sol-gel Derived Alumina - Nemati Kharat, Ali; Hamedinie, Leila (Asian Journal of Chemistry, 2010)
Several quaternary ammonium salts with different alkyl chain lengths were added to aluminium alkoxide sol; its transferring to a firm gel and then to nano-porous alumina were investigated. The BET surface area and pore size distribution measurements showed that pore size and surface area of γ-alumina can be altered by the type of quaternary anunonium salts. These measurements showed in presence of surface activity and micelle formation that there are two maxima for pore size distribution. Further analyses were done by infrared, XRD and thermal analysis.